Eastern Caribbean Currency Union : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Eastern Caribbean Currency Union (ECCU) has made significant progress in improving the quality and quantity of the macroeconomic statistics it produces and disseminates to the public. The Selected Issues Paper discusses prospects and challenges for credit unions in the ECCU. It reviews the current state of macroeconomic statistics, outlines progress that has been made, and identifies outstanding challenges. It also describes technical assistance to the region and presents the challenges for the production of macroeconomic statistics in small island states.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet